MAPPING AND EXPLORATION OF THE FUNCTIONS AND ELEMENTS OF ACEHNESE HOME GARDENS IN LUBOK SUKON VILLAGE, ACEH BESAR - Pratitou Arafat; Syarifah Nasywa Zhafira; Cut Nursaniah (Arsitekno, 2026)
This study examines the transformation and preservation of the pekarangan (homegarden) in Lubok Sukon, Aceh Besar, within the context of traditional Acehnese settlements. Lubok Sukon, a village where more than 30% of homes still retain traditional Acehnese architecture, has been designated as a tourist village, highlighting its cultural significance. While much scholarly attention has been given to Acehnese house architecture, the pekarangan has received less focus, despite its critical role in maintaining cultural identity. This research aims to examine the characteristics, functionality, and transformation of pekarangan in Lubok Sukon, considering both softscape and hardscape elements, spatial organization, function, and changes. Data were gathered through interviews, field observations, and literature reviews, and key features and spatial functions of the pekarangan were identified. Results indicate that the traditional Acehnese yard still retains significant cultural value, although certain elements have declined due to shifts in the community's livelihood. The study reveals that the addition of new functions, particularly tourism, has influenced the design and use of the pekarangan, while also decreasing the diversity of softscape and hardscape elements. The findings underscore the importance of the pekarangan as both a functional space and a reflection of the Acehnese cultural heritage, with implications for sustainable development and cultural preservation in the context of rural tourism.